MANZARALI DARAXTLARNING ASALARICHILIKDAGI O’RNI VA RO’LI TO’G’RISIDA - Hamidov Gulom Xamidovich; Mahsudova Gulnora Muxammadjonovna; Usmanova Tursinoy Erkinovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The place of ornamental trees in cities and villages and beekeeping today is very large. When expanding beekeeping in a wide space and expanding the scale of various ornamental trees.